Preliminary Study: Glycemic Index of Brown and White Rice Variant IR64 in Healthy Adult Men - Idril, Nur Irika; Diana, Aly; Wargahadibrata, Abdullah Firmansyah (Faculty of Medicine Universitas Padjadjaran, 2013)
Objective: To measure the glycemic index of brown and white rice in healthy adult men. Methods: The study was conducted in April 2010 at Universitas Padjadjaran, Jatinangor. Subjects of 21 healthy male students were randomly divided into 3 groups, which were given white bread (WB), white rice (WR) and brown rice (BR). Results: The results show that the highest and lowest average values of the blood glucose response was in the WR group at 30 minutes (126.9 mg/dL) and at 120 minutes (87.4 mg/dL), respectively. The glycemic index of brown rice (97.28) was lower compared to the white rice (99.26). Conclusions: Both WR and BR are classified as high glycemic index food. The higher glycemic index of brown rice, compared to the index found in other literatures, may be caused by differences in variant and/or production process. This study suggested the importance of evaluation of local products before promoting it to the community. Keywords: Blood glucose level, brown rice, glycemic index DOI: 10.15850/ijihs.v1n1.106